Social dynamics in the era of artificial intelligence - Luknar Ivana (Srpska Politička Misao)
Technological innovations intrigue the public and shape contemporary social dynamics. Modern society was created on the foundations of mega-changes. It is inherently complex to interpret as it undergoes constant transformation, making its analysis significantly more challenging. Modern society is dynamic, fluid, and networked into a complex and intertwined system of different contents and elements that cooperate with each other, overlap, and/or contradict each other. It is built and arises from the cooperation of various factors. Hence, a multidisciplinary approach was applied in this research paper. The primary purpose of the paper is to point out the importance of contemporary social dynamics, which are intensively changing under the influence of developed technology, especially under the influence of the development and application of artificial intelligence. This technology is perceived as the technology of the future and the technology that is the subject of intense global debate. The paper is structured into several chapters. After the introduction, the theoretical-methodological framework follows. Then, the next part of the paper is devoted to the interpretation of artificial intelligence from a sociological-political perspective. This technology is one of the key drivers of change in modern society and has the potential to dictate the pace of development of modern society. Therefore, the next chapter is devoted to the interpretation of contemporary social dynamics and the processes that laid the foundations for the emergence of modern society. The article also explains the processes that fueled the mega-changes in order to provide a comprehensive explanation of the current social dynamics. The value of a scientific article is reflected in the fact that it indicates the social effects of technology that have been reflected on a global level. Also, the paper encourages further interpretation of the researched topic, especially from the perspective of the application and further development of artificial intelligence.